3 - Leadership Development Schemes for Middle-level Academics in Merged Universities: The Case of Kyambogo University - Kasule, George Wilson (Journal of Higher Education in Africa, 2022)
Does the current generation of middle-level academics in most African universities, for example deans and heads of departments, adequately possess the leadership competence required to handle prevailing and future university obligations and challenges? In response to this question, this article, through a systematic literature review, explores the status quo of leadership competence of middle-level academics; factors that hinder leadership competence development; and measures needed to enhance leadership competence in African universities established out of mergers such as Kyambogo University in Uganda. Here, it is established that the status quo of leadership competence of middle-level academics, e.g., heads of departments, need improvement; and factors that hinder leadership competence development of middle-level academics can be perceived in two dimensions, i.e. “Institutional Factors” (e.g., poor working conditions, ineffective bureaucracy, etc.) and “Personal Factors” (e.g., lack of commitment, corruption etc.). Measures needed to enhance the leadership competence of academics include upgrading university facilities, adequately involving academics in university decision-making processes, and depoliticising university management and leadership, among other things. The article concludes that middle-level academics, such as Deans and heads of departments in African universities like Kyambogo, must do all it takes to improve their leadership competence, with other factors remaining constant if they want to meaningfully address the numerous grave challenges facing university education on the African continent.